The effect of price and service quality on customer satisfaction and loyalty customer waroeng steak and shake Medan - Satria Mirsya Affandy Nasution (Proceedings of AICS - Social Sciences, 2017)
Waroeng Steak Shake Medan is one of culinary businesses in Medan. The increase in customer loyalty at Waroeng Steak Shake Medan, is influenced by the variable of price in which determining the price provides understanding, influence, and improves bad customer loyality. The objective of the research was to examine and analyze the influence of price and service quality on customer satisfaction which, in turn, influenced customer loyality at Waroeng Steak Shake Medan, North Sumatra. The research used descriptive quantitative method with associative explanation approach. The study was conducted from July 2017 to August 2017. The population was 5,859 customers who were accidentally met by the researcher, based on Slovin formula, and 374 of them were used as the sampling, taken by using accidental sampling technique and path analysis. The result of the research showed that the variable of price had positive and significant influence on customer satisfaction, service quality had positive and significant influence on customer satisfaction, price and service quality simultaneously had positive and significant influence on customer satisfaction, price had positive and significant influence customer loyality, service quality had positive and significant influence on customer loyality, price had positive and significant influence on customer loyality through customer satisfaction, and service quality had positive and significant influence on customer loyality through customer satisfaction.